The zinc finger protein 3 of Arabidopsis thaliana regulates vegetative growth and root hair development - Benyó, Dániel; Bató, Emese; Faragó, Dóra; Rigó, Gábor; Domonkos, Ildikó; Labhane, Nitin; Zsigmond, Laura; Prasad, Melvin; Nagy, István; Szabados, László (Frontiers in Plant Science, 2024)
Zinc Finger Protein 3 (ZFP3) and closely related C2H2 Zinc finger proteins have been identified as regulators of abscisic acid signals and photomorphogenic responses during germination. Whether ZFP3 and related ZFP factors regulate plant development is however not known. ZFP3 overexpression reduced plant growth, limited cell expansion in leaves and compromised root hair development. The T-DNA insertion zfp3 mutant and transgenic lines with silenced ZFP1, ZFP3, ZFP4 and ZFP7 genes were similar to wild type plants or had only minor differences in plant growth and morphology, probably due to functional redundancy. RNAseq transcript profiling identified ZFP3-controlled gene sets, including targets of ABA signaling with reduced transcript abundance. The largest gene set which was downregulated by ZFP3 encoded regulatory and structural proteins in cell wall biogenesis, cell differentiation and root hair formation. Chromatin immunoprecipitation confirmed ZFP3 binding to several target promoters. Our results suggest that ZFP3 and related ZnF proteins can modulate cellular differentiation and plant vegetative development by regulating the expression of genes implicated in cell wall biogenesis.